Management of Nematodes and Soil Fertility with Sunn Hemp Cover Crop - Zane Joseph Grabau (EDIS)
Sunn hemp, Crotalaria juncea L. is a rapidly growing crop used for fiber production in India and Pakistan. It is popular as a green manure in many tropical and subtropical areas in the world, and is also valued because it suppresses weeds, slows soil erosion, and reduces root-knot nematode populations. Recently, as cultivars adapted for seed production in the southeastern United States have been introduced, there is a growing interest in rotating sunn hemp with agronomic crops in the southern United States and in using sunn hemp as a summer cover crop in Florida and other southeastern states. This publication informs agricultural professionals about the impacts of sunn hemp cover cropping on soil fertility and plant-parasitic nematodes.